Socioeconomic Determinants of Diarrhea among Under-Five Children in Bangladesh: Do Education and Wealth Matter? - Alauddin, Sharlene; Haque, M. Ershadul (Journal of Maternal and Child Health, 2021)
Background: The purpose of this study is to assess the current status of diarrhea among the under-five children in Bangladesh by exploring the risk factors which are associated with this disease. Subjects and Method: In this study, a nationally representative cross-sectional data had been used and the sample of women having under five children was selected by using a two stage stratified sampling method. A total of 7410 under five children were included. The dependent variable of this study was the status of diarrhea disease in the two weeks preceding the survey. The independent variable was education-wealth composition along with some other important variables such as age of children, delivery by caesarean section, migration status, mother’s age at birth, type of residence, source of toilet facility, sources of drinking water. The bivariate analysis was chi-square. The multivariate analysis was a multiple logistic regression. Results: According to this research study, education and wealth didn’t show any impact individually in the logistic regression model but when we excluded education and wealth from the model and create it is composition, it worked as a significant influential factor of diarrhea disease in Bangladesh. Women who were literate and their wealth status was not rich (OR= 0.64; 95% CI= 0.43 to 0.96; p= 0.030), women who were literate and rich (OR= 0.55; 95% CI= 0.35 to 0.88; p = 0.012) had significant association with childhood diarrhea. In addition to that only children age between 6-23 months (OR= 3.49; 95% CI= 2.23 to 5.48; p<0.001) and 24-35 months (OR= 1.75; 95% CI= 1.08 to 2.85; p= 0.023) worked out as a significant predictor of childhood diarrhea. Conclusion: This study was expected to help to build up a proper understanding about the socio-economic factors in order to reduce the childhood diarrhea in Bangladesh.